2021
DOI: 10.15420/ecr.2021.16.po3
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Peptide of Ganoderma lucidum Reduces Endothelial Injury in Stable Angina and High-risk Patients

Abstract: This study aims to prove the effect of the polysaccharide peptide (PsP) of Ganoderma lucidum to reduce endothelial injury and improve endothelial function. Material and methods:This is a clinical trial with pre-post-test design, conducted in 40 high-risk and 40 stable angina patients, determined based on the 2016 European Society of Cardiology guideline for stable coronary artery disease.Stable angina and high risk patients were given PsP 750 mg/day in three divided doses for 90 days in addition to their regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the attractive nature of G. lucidum has been proven to be related to GLPP, which is known as a significant constituent of G. lucidum with a molecular weight of ∼5 × 10 4 Da and a polysaccharide content of up to 87.17%, containing 16 amino acids with a total amino acid content of 5.04% (10). Previous studies have shown that GLPP has diverse bioactivities such as antioxidant, memory-enhancing, antitumor, oxidative stress-reducing, fatty liver-reducing, liver and kidney-protecting, and sleep-protecting effects, and its most important biological activity is to enhance host immunity by enhancing immune cell function and promoting the release of immune factors (11)(12)(13)(14)(15)(16)(17). The enhanced immune function of polysaccharides has benefited several areas of medical research, for instance, by reducing the side effects associated with treating cancer.…”
mentioning
confidence: 99%
“…However, the attractive nature of G. lucidum has been proven to be related to GLPP, which is known as a significant constituent of G. lucidum with a molecular weight of ∼5 × 10 4 Da and a polysaccharide content of up to 87.17%, containing 16 amino acids with a total amino acid content of 5.04% (10). Previous studies have shown that GLPP has diverse bioactivities such as antioxidant, memory-enhancing, antitumor, oxidative stress-reducing, fatty liver-reducing, liver and kidney-protecting, and sleep-protecting effects, and its most important biological activity is to enhance host immunity by enhancing immune cell function and promoting the release of immune factors (11)(12)(13)(14)(15)(16)(17). The enhanced immune function of polysaccharides has benefited several areas of medical research, for instance, by reducing the side effects associated with treating cancer.…”
mentioning
confidence: 99%